THE INTERNET AS A RESOURCE FOR LANGUAGE LEARNING AND TEACHING (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This thesis examines the transformative role of the internet as a multi-dimensional resource in contemporary foreign language learning and teaching. Modern educational paradigms necessitate a transition from conventional textbook-bound curricula to interactive, digitally mediated environments that enhance communicative competence, cognitive independence, and collaborative learning. The research outlines the key theoretical frameworks, including Computer-Assisted Language Learning (CALL) and Mobile-Assisted Language Learning (MALL), that validate internet integration. Furthermore, it explores the dual perspective of web resources, highlighting specific benefits for learners, such as access to authentic input and enhanced autonomy, as well as advantages for educators, including digital curriculum curation and artificial intelligence integration. Finally, the study addresses critical challenges, such as information overload and the digital divide, offering practical  pedagogical  recommendations  for  sustainable  hybrid  classrooms.
Keywords: The rapid acceleration of globalization, cross-border digital communication, and technological innovation has established foreign language proficiency as a fundamental requirement of the 21st century. Consequently, traditional instructional methodologies, which heavily prioritize rote memorization, explicit grammar instruction, and static textbook reading, are increasingly perceived as inadequate for producing fluent speakers. Modern applied linguistics emphasizes communicative competence, demanding educational environments where target languages are practiced dynamically and contextualized realistically.